Gyro-spintronic material science using vorticity gradient in solids - Yukio Nozaki; Hiroaki Sukegawa; Shinichi Watanabe; Seiji Yunoki; Taisuke Horaguchi; Hayato Nakayama; Kazuto Yamanoi; Zhenchao Wen; Cong He; Jieyuan Song; Tadakatsu Ohkubo; Seiji Mitani; et al. (Science and Technology of Advanced Materials, 2024)
We present a novel method for generating spin currents using the gyromagnetic effect, a phenomenon discovered over a century ago. This effect, crucial for understanding the origins of magnetism, enables the coupling between various macroscopic rotational motions and electron spins. While higher rotational speeds intensify the effect, conventional mechanical rotations, typically below 10,000 RPM, produce negligible results comparable to geomagnetic fluctuations, limiting applied research. Our studies demonstrate that spin current generation comparable to that of rare metals can be achieved through atomic rotations induced by GHz-range surface acoustic waves and the rotational motion of conduction electrons in metallic thin films with nanoscale gradient modulation of electrical conductivity. These effects, termed the acoustic gyromagnetic effect and the current-vorticity gyromagnetic effect, are significant in different contexts. The acoustic gyromagnetic effect is notable in high conductivity materials like aluminum and copper, which are more abundant than conventional spintronics materials with strong spin-orbit interactions (SOIs). Conversely, the current-vorticity gyromagnetic effect requires a large conductivity gradient to produce current vorticity efficiently. This is achieved by using composition gradient structures from highly conductive metals to poorly conductive oxides or semiconductors. Consequently, unlike traditional strong-SOI materials, we can create highly efficient spin current generators with low energy dissipation due to reduced Joule loss.